A comparative study on the migration of minor phase globule in different-sized droplets of Fe-58wt.%Sn immiscible alloy. (15th July 2019) - Peng, Yinli; Wang, Qiang; Wang, Nan
Abstract: The migration behaviors of minor-phase globules are comparatively studied inside (radius=) 200 μm and 400 μm droplets based on the model of Fe-58wt.%Sn alloy under reduced-gravity condition. It was found that the final relative positions of same-sized globules are not dependent on the droplet sizes, although the globule's migrating velocity and lifetime inside different-sized droplet alloys are different. This finding is contrary to the conventional understanding that the droplet size can exert great influence on the microstructures by controlling Marangoni motion, and moreover offers a new insight into how to design the desired structures in the droplet immiscible alloy. Graphical abstract: Unlabelled Image